2000
DOI: 10.1128/iai.68.3.1450-1456.2000
|View full text |Cite
|
Sign up to set email alerts
|

CpG Oligodeoxynucleotides Act as Adjuvants for Pneumococcal Polysaccharide-Protein Conjugate Vaccines and Enhance Antipolysaccharide Immunoglobulin G2a (IgG2a) and IgG3 Antibodies

Abstract: Pneumococcal polysaccharide-protein conjugate vaccines elicit antipolysaccharide antibodies, but multiple doses are required to achieve protective antibody levels in children. In addition, the immunogenicity of experimental multivalent pneumococcal conjugate vaccines varies with different polysaccharide serotypes. One strategy to improve these vaccines is to incorporate an adjuvant to enhance their immunogenicity. Synthetic oligodeoxynucleotides containing unmethylated CpG motifs (CpG ODN) are adjuvants that p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
37
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(42 citation statements)
references
References 32 publications
5
37
0
Order By: Relevance
“…Indeed, CpG ODN has been shown to enhance Ab responses against S. pneumoniae polysaccharide types 19F and 6B (33). Our previous study showed that mice given nasal recombinant protective Ag of anthrax toxin plus CpG ODN exhibited high levels of protective Ag- Mice were nasally immunized weekly for four consecutive weeks with 1 mg PspA, 50 mg pFL, and 10 mg CpG ODN and for 3 consecutive wk with 5 mg PspA, 50 mg pFL, and 10 mg CpG ODN in young adult and aged mice, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, CpG ODN has been shown to enhance Ab responses against S. pneumoniae polysaccharide types 19F and 6B (33). Our previous study showed that mice given nasal recombinant protective Ag of anthrax toxin plus CpG ODN exhibited high levels of protective Ag- Mice were nasally immunized weekly for four consecutive weeks with 1 mg PspA, 50 mg pFL, and 10 mg CpG ODN and for 3 consecutive wk with 5 mg PspA, 50 mg pFL, and 10 mg CpG ODN in young adult and aged mice, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…17,18 We thus explored whether the use of a TLR9 agonist (CpG ODNs) expected to mimic some of the cosignals provided by whole bacteria could modulate the amplitude and duration of the Ab response to PS3. In a coadministration protocol, CpG ODNs have been reported to amplify the Ab response to PS-protein conjugates 19,20 or to NP-Ficoll but not to a plain PS vaccine. 21 To reconsider the effect of TLR agonists on TI B-cell responses, we conducted experiments in which CpG1668 was administrated subcutaneously before immunization, at the time of immunization, or after immunization with PS3.…”
Section: Cpg1668 Enhances the Ab Response To Ps3 In A T Cell-independmentioning
confidence: 99%
“…We thus wished to determine whether the IgG anti-PspA and IgG anti-PPS14 responses to conjugate, in the absence or presence of adjuvant, were also dependent on IL-1R1 Ϫ/Ϫ signaling. Coinjection of conjugate with a TLR ligand can markedly enhance the subsequent humoral immune response (45,50,51), which could, in theory, influence its relative dependence on costimulation with endogenous IL-1.…”
Section: Cd4 ϩ T Cells From Pn14-immunized Il-1r1mentioning
confidence: 99%